Člověk má dělat to, co ho baví a čemu rozumí - Sládeček J. (Centrum pro podporu počítačové grafiky ČR s.r.o., 2014)
Profil ateliéru architekta Miroslava Gebase, jeho zásadách a způsobu architektonické práce

Profile of an architectural studo of Miroslav Gebas, his principles and way of architectural work
One should do what he enjoys and what he understans
Keywords: profile; architectural studio; Miroslav Gebas; architect